Vertical Wind Turbine Coupled with Modified Synchronous Generator for Portable Power Generation - Agus Ulinuha; M. Burhanduin Ubaidillah (Urecol Journal. Part E: Engineering, 2021)
Coastal region normally has sufficient wind power that has not been properly utilized. On the other hand, some places in this region do not have electricity supply from the utility due to some reason. People activity in these areas may need some electricity at least for lighting the area in the evening. For the purpose of generating electricity, a portable power generation is developed to use the wind power and used to supply the power for the light. Wind power plants have so far used propellers with horizontal configurations. In this model, the blades used in propellers have limited dimensions due to mechanical considerations. In addition, the direction of the propeller needs to be directed toward the wind flow, so that a steering wheel and a rotating base are required. To overcome this problem, it is necessary to utilize a number of wind impulse blades placed on the vertical axis. In addition to the expectation to obtain greater thrust, no mechanical equipment is necesary to direct the turbine toward the direction of wind flow. These advantages are expected to increase the output voltage of the generator coupled to it. The generator used in this research is a modified induction motor with some additional magnetic poles to become synchronous generator. The generated power is used to charge a battery which is used to power the light at the night. Small scale generator prototype was developed and tested for coastal locations or other open spaces to obtain wind flow with sufficient power to drive turbine blades.